2022
DOI: 10.1111/jiec.13239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing recycling, displacement, and environmental impacts using an economics‐informed material system model

Abstract: Material production drives an increasingly large fraction of CO 2 -equivalent emissions. Material efficiency strategies such as recycling serve to reduce these emissions.Current analyses of the effectiveness of such strategies do not include economically induced rebound effects, overestimating the associated environmental benefits. We present a dynamic supply chain simulation model for copper through 2040 incorporating inventory-driven price evolution, dynamic material flow analysis, and life cycle assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In light of this, it is important to conduct a careful scientific investigation in order to establish whether a circular system truly contributes to decarbonization, as opposed to merely observing the CU indicators. 49 As in the case of the CU indicators, improvements in RP were not uniformly consistent with reductions in CF. That improvements in MFIs can, at least in some cases, be inconsistent with reductions in carbon emissions is an important lesson.…”
Section: Focusing On Drivers Of Change In Mfismentioning
confidence: 81%
See 2 more Smart Citations
“…In light of this, it is important to conduct a careful scientific investigation in order to establish whether a circular system truly contributes to decarbonization, as opposed to merely observing the CU indicators. 49 As in the case of the CU indicators, improvements in RP were not uniformly consistent with reductions in CF. That improvements in MFIs can, at least in some cases, be inconsistent with reductions in carbon emissions is an important lesson.…”
Section: Focusing On Drivers Of Change In Mfismentioning
confidence: 81%
“…We have demonstrated that, in some sectors, improvements in the CU indicators did not produce CF reductions. In light of this, it is important to conduct a careful scientific investigation in order to establish whether a circular system truly contributes to decarbonization, as opposed to merely observing the CU indicators …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, future research should extend this methodology to study the effects of covariates other than price and income. For example, researchers can study the effect of sector-specific variables (e.g., automotive sales, electricity demand), region-specific variables (e.g., urbanization), or recycling rates, which impacts demand through feedback (Ryter et al, 2021(Ryter et al, , 2022. Adding more covariates can allow interesting analyses such as studying the impact of vehicle electrification (by using EV sales as an inflow variable that impacts demand), transition to renewable energy, and increased recycling rates on metal consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Given we have already argued for the importance of price feedbacks, we will focus on approaches that incorporate market clearing of both supply and demand (for common supply and demand modeling approaches, see the review by Watari et al., 2021). Broadly speaking, metals markets are studied using (i) econometric models (Fisher et al., 1972; Fu et al., 2017; Watkins & McAleer, 2004), (ii) agent‐based models (Bollinger et al., 2012; Cao et al., 2021; Riddle et al., 2015), and (iii) system dynamics models (Elshkaki, 2013; Sprecher et al., 2015a; Sverdrup et al., 2017) or a combination of the three (Ryter et al., 2022). Econometric models often assume a partial equilibrium between demand and supply which are both estimated via statistical relationships with variables such as economic growth and population (Zink et al., 2016, 2018).…”
Section: Introductionmentioning
confidence: 99%